The effect of brand’s official instagram account toward offline purchase intention: study in high and low involvement product - Subagio, Ratih Anjani (Journal of Entrepreneurial Economics, 2025)
Background: The increasing use of social media by businesses has transformed how companies interact with consumers. Companies leverage social media content to engage with their audience, influencing their perceptions and purchasing decisions. This study applies the Stimulus-Organism-Response (S-O-R) theory, where social media factors such as content quality and brand interactivity act as stimuli (S), triggering emotional and cognitive reactions—hedonic and utilitarian motives—which lead to consumer engagement (O) and ultimately drive brand awareness and offline purchase intention (R). Methods: The study employs structural equation modeling (SEM) to analyze data collected from 797 respondents. A multi-group analysis is conducted based on product involvement levels, distinguishing between high-involvement and low-involvement products. Findings: Content quality and brand interactivity positively influence hedonic and utilitarian motives. However, brand interactivity does not significantly affect utilitarian motives. Hedonic and utilitarian motives enhance consumer engagement with the brand, which in turn strengthens brand awareness on social media. Increased consumer engagement and brand awareness on social media lead to higher offline purchase intention. Consumer behavior differs between high-involvement and low-involvement products, affecting how content quality and brand interactivity drive hedonic and utilitarian motivations. Conclusion: The study confirms the applicability of S-O-R theory in social media marketing, emphasizing the role of content quality and brand interactivity in shaping consumer engagement and purchasing behavior. The findings suggest that brands should actively utilize official social media accounts to bridge the online-offline gap in retail, helping consumers fulfill both hedonic and utilitarian needs before making offline purchases. Novelty/Originality of this article: This study extends the S-O-R theory into the context of social media marketing, providing new insights into how content quality and brand interactivity influence consumer motives, engagement, and purchasing behavior. Additionally, the multi-group analysis highlights differences in consumer responses based on product involvement levels, offering valuable strategic implications for businesses optimizing their social media presence.